2015
DOI: 10.3329/jesnr.v7i2.22221
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heavy Metals (Pb, Cd, Cr, Cu, Hg and Fe) of the Turag River in Bangladesh

Abstract: The study was conducted to assess the concentration level of heavy metals in water of the Turag river during the months from January to March, 2014. The level of Pb, Cd, Cr, Cu, Hg and Fe ranged from 0.002-0.005 ppm, BDL (Below Detection Level)-0.03 ppm, 0.007-0.024 ppm, 0.03-0.15 ppm, BDL (Below Detection Level)-0.00024 and 0.78-6.33 ppm, respectively. The concentration level of heavy metals in water did not exceed the permissible limit except Fe. This result was obtained because of river water is always flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Normally the order of Hg accumulation in fish is kidney > liver > muscle > gill (Abdel-Baki, 2011). Afrin et al (2014) found Hg as not detectable in Ashulia bridge area of the Turag river water.…”
Section: Mercury (Hg)mentioning
confidence: 81%
See 2 more Smart Citations
“…Normally the order of Hg accumulation in fish is kidney > liver > muscle > gill (Abdel-Baki, 2011). Afrin et al (2014) found Hg as not detectable in Ashulia bridge area of the Turag river water.…”
Section: Mercury (Hg)mentioning
confidence: 81%
“…The highest value (46.86 mg/kg) of Fe was observed in species 2 in March and the lowest (4.05 mg/kg) was observed in species 3 in February (Table 2). Afrin et al (2014) found the highest value of Fe in Ashulia bridge area of the Turag river water as 6.33 mg/L in March, 2014.…”
Section: Mercury (Hg)mentioning
confidence: 91%
See 1 more Smart Citation
“…Regarding heavy metals of Turag River, the average values of Ni in three distinct seasons were 0.019 mg/L (pre-monsoon); 0.017 mg/L (monsoon) and 0.021 mg/L (post-monsoon) [25]. The highest value of Cd and Cr was observed in the Turag River were (0.03 ppm) and (0.02 ppm) [33]. The standard values of Cd for drinking, irrigation and livestock water are 0.005, 0.01 and 0.5 ppm, respectively [23].…”
Section: Heavy Metals In Water Samplementioning
confidence: 99%
“…Загрязнение железом речной воды, возможно, было обусловлено сбросами предприятий фармацевтической, кожевенной и текстильной промышленности. В исследовании [5] отмечено, что содержание Fe в воде р. Тураг находилось в диапазоне от 0,78 до 6,33 мг•л −1 ; эти значения гораздо выше результатов мониторинга вод р. Падма в 2014-2017 гг.…”
Section: результаты и обсуждениеunclassified